A Case of Refractory Polymyositis Successfully Treated With Abatacept Monotherapy - Mehmet ÇAĞLAYAN,; Hüseyin IŞIK,; Pelin OKTAYOGLU, (Archives of Rheumatology, 2020)
Polymyositis (PM) is an autoimmune disease progressing in the form of a break down of the muscles that is induced by chronic inflammation in skeletal muscles. Muscle weakness is painless and concentrates on proximal muscles, involving the pectoral and pelvic girdle. If the disease is not treated properly, it may progress and lead to a considerable decrease in the quality of life. Its conventional treatment involves drugs that suppress inflammation such as steroids, methotrexate, azathioprine, and intravenous immunoglobulin. However, conventional treatment may prove insufficient to halt the progression of the disease and offer only a limited improvement because of the adverse effects it causes in some patients. In this article, we present a 48-year-old female patient diagnosed with PM nearly 13 years ago that did not sufficiently respond to the pharmaceutical agents that were indicated for the conventional treatment of the disease and developed femoral head avascular necrosis because of the treatment and was, in the end, successfully treated with abatacept monotherapy at our clinic.